High‐Performance Flexible Schottky DC Generator via Metal/Conducting Polymer Sliding Contacts. (6th August 2021) - Yang, Ruizhe; Benner, Matthew; Guo, Zipeng; Zhou, Chi; Liu, Jun
Abstract: Dynamic Schottky direct‐current (DC) generators hold great promise for ambient mechanical energy harvesting as it overcomes the low‐current output limitation in conventional approaches. However, the lack of a fundamental understanding of DC generation in conducting polymer‐based Schottky generators has hindered their application for self‐powered wearable and implantable electronics. Here, a high‐performance, flexible Schottky DC generator with metal/conducting polymer sliding contact system is demonstrated, which exhibits a large current density ( J ) up to 20 A m –2 for single contact geometry and a scaled‐up DC output reaching 200 µA ( J = 0.73 A m –2 ) and 0.8 V. The design of flexibility in such a Schottky DC generator is inherited from the long‐chain polymer concept, leading to the demonstration of a variety of device configuration of free‐standing thin film, supported thin film and nanocomposite prototype toward practical applications. It is revealed that the sliding junctions may exhibit a different mechanical energy conversion mechanism compared to the compressive conducting polymer Schottky junctions. It is also proven that the magnitude and polarity of DC generation is determined by the Schottky contact formation and interfacial electric field. The concept of a flexible Schottky generator not only shows great promise for next‐generation, self‐powered wearable devices, but also provides potential mechanisms for developing novel wearable sensors. Abstract : The dynamic Schottky DC generator holds great promise for mechanical energy harvesting as it generates a continuous DC output with a large current density. Here, a high‐performance, flexible Schottky DC generator with metal/conducting polymer sliding contact system is demonstrated. The concept not only shows great prospect for self‐powered wearable devices, but also provides potential mechanisms for developing novel wearable sensors.